(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The basic principle of Hydroelectric Generator is used in Electricity generation by Floating Hydro-Turbine. Every aspect of a hydro system revolves around Head and Flow. The generation of electricity is simply a conversion of one form of power to another one. This research describes design and development of wave turbine that could be used in local seashore of konkan region of Maharashtra, India